Musa sp. paradisiaca Cultivar Gopi and Clonal fidelity Assessment using ISSR Marker (Plant Tissue Culture and Biotechnology, 2019)
Attempt was made towards optimizing an in vitro shoot multiplication of banana cultivar Gopi with subsequent assessment of genetic stability. Experiments on enhanced shoot multiplication were conducted in MS fortified with BAP, Kn and 2-iP (4 mg/l) for a period of 8 weeks. Administration of exogenous root inducing growth regulator was eliminated to reduce culture investment and economy. Treatment with BAP supplemented medium proved to be optimum for shoot multiplication whereas 2-iP produced satisfactory results for shoot elongation. Long term incubation in all the treatments had been favorable for developing efficient root system. Hardening of in vitro grown plantlets showed high rate of survival (95%) upon transfer to potted soil. Assessment of clonal fidelity through inter simple sequence repeats (ISSR) analysis revealed 100% uniformity.